Kepribadian Pustakawan yang Humanis dalam Meningkatkan Layanan Perpustakaan (Aktualisasi Diri) Di Perpustakaan Universitas 17 Agustus 1945 Semarang: Humanist Library Personality In Improving Library Services (Self-Actualization) In Library Of University August 17,1945 Semarang - Arin Luthfiyah; Anis Masruri (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The librarian profession is not only required to be proficient at work, but must be attractive in appearance, librarians face challenges and demands from net generation users. Being a professional librarian does not use the palms of the hands but it takes a lot of effort to achieve this, including the importance of social interaction in association to have a humanist face, which means that a librarian must be able to provide excellent service to users, so that librarians will gain the trust of their users. Librarians must also apply 3S etiquette (simple, harmonious, and polite) as well as to form a superior, inclusive, and humanist person who at least has POWER, namely, positive attitude, other people, words, expand, and realize. It is expected that librarians are able to maintain the stability of the quality of library services.